2023
DOI: 10.1103/physrevb.107.075303
|View full text |Cite
|
Sign up to set email alerts
|

Layer-dependent zero-line modes in antiferromagnetic topological insulators

Abstract: Recently, the magnetic domain walls have been experimentally observed in antiferromagnetic topological insulators MnBi 2 Te 4 . Here we study the intrinsic topological zero-line modes (ZLMs) that appear along the domain walls, and find that these ZLMs are layer dependent in MnBi 2 Te 4 multilayers. We reveal the role of the spatial layer degree of freedom and magnetic domain wall configurations in determining the electronic transport properties and the distribution of the ZLMs in antiferromagnetic topological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We expect that our results will also be relevant in this platform. Theoretical predictions for layer-dependent zero-line modes in antiferromagnetic topological insulator multilayer structures based on MnBi 2 Te 4 [56] suggest that our theory can also be applied in that context. An important caveat when comparing our results to experiments concerns the idealized step-like mass term considered here.…”
Section: Discussionmentioning
confidence: 85%
“…We expect that our results will also be relevant in this platform. Theoretical predictions for layer-dependent zero-line modes in antiferromagnetic topological insulator multilayer structures based on MnBi 2 Te 4 [56] suggest that our theory can also be applied in that context. An important caveat when comparing our results to experiments concerns the idealized step-like mass term considered here.…”
Section: Discussionmentioning
confidence: 85%
“…It has been found that graphene-like materials can exhibit abundant topological phases under different external fields applied to the whole system, [11][12][13][14][15] and the side potential applied to the boundary of the system is also crucial for generating and manipulating topological phases and corresponding edge states. [16,17] In particular, a large number of zero-line modes (ZLMs) [18][19][20] that can arise from the interface separating different topological phases have been found in addition to outer edge states [11,[21][22][23] induced at the interface between topological phases and the topologically trivial vacuum. In particular, ZLMs are related not only to the Chern numbers but also to the valley Chern numbers, which are also known as kink states and inner edge states, respectively.…”
Section: Introductionmentioning
confidence: 99%